2021
DOI: 10.1186/s12889-021-10700-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in health behavior and weight outcomes following enhanced afterschool programming participation

Abstract: Background The United States needs to increase access to effective obesity prevention and treatment programming for impoverished youth at risk for health disparities. Although recommended, schools have difficulty consistently implement evidence-based obesity programing. We report on the effectiveness of adding structured nutrition education and minimum physical activity (PA) requirements to standard middle school after-school programming. Methods U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…EST at the microsystem level, the results showed improvement in physical activity, exercise behaviors, knowledge about obesity and NCDs prevention among students. This finding corresponds with the findings of previous studies focused on promoting exercise in schoolage children (31) and programs focused on knowledge about food and nutrition combined with promoting afterschool exercise (32) . The findings indicate that promoting exercise at school is efficient in improving the overall physical fitness for students (31) .…”
Section: Discussionsupporting
confidence: 91%
“…EST at the microsystem level, the results showed improvement in physical activity, exercise behaviors, knowledge about obesity and NCDs prevention among students. This finding corresponds with the findings of previous studies focused on promoting exercise in schoolage children (31) and programs focused on knowledge about food and nutrition combined with promoting afterschool exercise (32) . The findings indicate that promoting exercise at school is efficient in improving the overall physical fitness for students (31) .…”
Section: Discussionsupporting
confidence: 91%
“…Their strategy reinforced healthy eating habits, good physical activity, and rest in the afterschool period. Nonetheless, their results vary from those achieved by the U4HK strategy in that they only show non-significant improvements in behavior towards food (17).…”
Section: Discussionmentioning
confidence: 62%
“…Some authors report the necessity to include the afterschool period in these health promotion activities. For instance, Rieder et al carried out a longitudinal three-year study with 76 predominantly Latino schoolchildren in the United States, with pre and post-intervention measurements (17). Their strategy reinforced healthy eating habits, good physical activity, and rest in the afterschool period.…”
Section: Discussionmentioning
confidence: 99%
“… 23 28 29 Moreover, the Games have increased the Olympic values education and improved the attention to physical training in Chinese schools, and a large number of primary and secondary schools have opened up their sports facilities to the public, 22 which may also increase the possibility and accessibility of exercise for children after school, alone or together with their families. School-based physical activities are proven beneficial to the obesity prevention or treatment for children with overweight, 30 and physical activities after school are also reported to result in positive improvements in children’s weight outcomes 31 to avoid underweight. Notably, previous studies indicated that Chinese boys had higher prevalence of obesity and were more likely to be satisfied with their physical activity level than girls, 32 which may be a potential explanation for the sex difference in the association between the BOG and obesity found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…obesity prevention or treatment for children with overweight, 30 and physical activities after school are also reported to result in positive improvements in children's weight outcomes 31 to avoid underweight. Notably, previous studies indicated that Chinese boys had higher prevalence of obesity and were more likely to be satisfied with their physical activity level than girls, 32 which may be a potential explanation for the sex difference in the association between the BOG and obesity found in our study.…”
Section: Original Researchmentioning
confidence: 99%